"Hero Behind the Curtain": Multicultural workers in culturally diverse dementia care: Developing topics. (7th December 2020) - Antoniades, Josefine; Croy, Samantha; Kent, Mike; Ellis, Katie; Brijnath, Bianca
Abstract: Background: The number of culturally and linguistically diverse (CALD) people with dementia in Australia is projected to rise. CALD groups are diagnosed later and access care services less than other Australians. Accessing services is fraught with barriers for CALD communities and service providers face challenges in meeting the needs of CALD clients. We explore the experiences of multicultural service providers working with members of their own communities, focusing on strategies employed to facilitate access and provide care to CALD people with dementia and their families. Methods: We conducted 25 in‐depth video‐recorded interviews with multicultural service providers working with CALD clients in Victoria, New South Wales and Western Australia. Interviews were conducted both in language and in English, and were translated and transcribed verbatim. The data were analysed thematically. Results: Participants identified cultural expectations around family caring and stigma associated with extrafamilial care as significant challenges, leading to reluctance to engage with services. Drawing on understandings of different communities' approaches to dementia and norms around care for older people, participants were able to address concerns and enable access to much needed services in culturally acceptable ways. In residential aged care, participants described strategies to make aged care more palatable, emphasising the family's continued role in care as they allowed providers to 'take over the dirty jobs'. Familiarity and a sense of belonging were fostered for clients with dementia through attention to culturally‐specific needs, whilst building relationships with families to address deep‐seated guilt at placing their loved ones in residential care. Conclusions: The perspectives of multicultural workers in CALD dementia care provide insight into opportunities for provision of culturally‐appropriate care. The study highlights the significant contributions of multiethnic workers in providing care that is flexible, person‐centred and attentive to cultural needs of CALD clients with dementia and their families.